If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 8 = 2m + -12 Reorder the terms: 8 + 6m = 2m + -12 Reorder the terms: 8 + 6m = -12 + 2m Solving 8 + 6m = -12 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 8 + 6m + -2m = -12 + 2m + -2m Combine like terms: 6m + -2m = 4m 8 + 4m = -12 + 2m + -2m Combine like terms: 2m + -2m = 0 8 + 4m = -12 + 0 8 + 4m = -12 Add '-8' to each side of the equation. 8 + -8 + 4m = -12 + -8 Combine like terms: 8 + -8 = 0 0 + 4m = -12 + -8 4m = -12 + -8 Combine like terms: -12 + -8 = -20 4m = -20 Divide each side by '4'. m = -5 Simplifying m = -5
| 9t-7=3t-5 | | 20y-6=18y+4 | | 4(6a+2)=-88 | | -2(3s-3)-6=-3(6s+0)-5 | | 3(-6t+4)=-5t+2(t-9) | | 14+b=13-3b | | 12x^4=2x^2+4 | | 2ysquare=12y-5y | | 4y+3=127 | | X^2-9y^2+6x-36y-36=0 | | 10=(6+9b)+7b | | 3log(2)=9log(x) | | x+6=4x-21 | | 6x+8+2x+4= | | 5.36-0.4m=26.8-0.4m | | 3(4x+3)+4x=61 | | (35-2x)(70-2x)= | | Y^2=2px+p^2 | | 13x+2=13x-4 | | (x-b)=x | | 2x-5/7=8/25 | | x+(-16)=-12 | | nx=3y-5 | | 2/3(m-8)=9 | | 35=3x+2(x-5) | | 24000/X=0 | | 0.2x-3.4=0.5x-2.5 | | 6=1-3p | | 130=24x+2 | | 18x-6=120 | | 6=1-3p+2 | | 5x-2=2(5x+1)-1 |